A novel potent ABCB1 modulator, phenethylisoquinoline alkaloid, reverses multidrug resistance in cancer cell - Sugisawa, Norihiko (Mol Pharm, 2018)
ATP-binding cassette (ABC) transporters, which are concerned with the efflux of anticancer drugs from cancer cells, have a pivotal role in multidrug resistance (MDR). In particular, ABCB1 is a well-known ABC transporter that develops MDR in many cancer cells. Some ABCB1 modulators can reverse ABCB1-mediated MDR, however no modulators with clinical efficacy have been approved. The aim of this study was to identify novel ABCB1 modulators by using high-throughput screening. Of 5861 compounds stored at Tohoku University, 13 compounds were selected after the primary screening via a fluorescent plate reader-based calcein acetoxymethylester (AM) efflux assay. These 13 compounds were validated in a flow cytometry-based calcein AM efflux assay. Two isoquinoline derivatives were identified as novel ABCB1 inhibitors, one of which was a phenethylisoquinoline alkaloid, (±)-7-benzyloxy-1-(3-benzyloxy-4-methoxyphenethyl)-1,2,3,4-tetrahydro-6-methoxy-2-methylisoquinoline oxalate. The compound, a phenethylisoquinoline alkaloid, was subsequently evaluated in the cytotoxicity assay and shown to significantly enhance the reversal of ABCB1-mediated MDR. In addition, the compound activated the ABCB1-mediated ATP hydrolysis and inhibited the photolabeling of ABCB1 with [(125)I]iodoarylazidoprazosin. Furthermore, the compound also reversed the resistance to paclitaxel without increasing the toxicity in the ABCB1-overexpressing KB-V1 cell xenograft model. Overall, we concluded that the newly identified phenethylisoquinoline alkaloid reversed ABCB1-mediated MDR through direct interaction with the substrate-binding site of ABCB1. These findings may contribute to the development of more potent and less toxic ABCB1 modulators, which could overcome ABCB1-mediated MDR.